Halal Fast Food Loyalty: Brand Image as a Mediator of SMMA, Certification, and CSR - Rizal, Mukhammad; Hapsari, Raditha Dwi Vata; Yulianti, Ida (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2026)
This study examines how Social Media Marketing Activities (SMMA), halal certification, and Corporate Social Responsibility (CSR) influence consumer loyalty in halal fast-food, with brand image as a mediator. Grounded in the Stimulus–Organism–Response framework, data from 483 Muslim Generation Z consumers of KFC in Malang City were analyzed using PLS-SEM. The results show that SMMA and CSR positively affect loyalty both directly and indirectly through brand image. Halal certification has no direct effect but indirectly shapes loyalty via brand image. The findings suggest that halal certification functions as a baseline expectation rather than a differentiating factor. This study contributes to Islamic marketing by clarifying the shifting role of institutional religious standards and offers managerial implications for strengthening digital engagement, CSR authenticity, and halal communication.